An Energy-Efficient Smart Building System using Autonomous Networks - Kumari P.; Gupta H.P. (My University, 2025)
A sensing system is an emerging paradigm for making smart buildings. The system's success depends on correctly communicating the sensing information from a building to the end-user within the given constraints. An autonomous network can maintain and reconfigure itself in a dynamic environment without human intervention. A sensing system using an autonomous network takes decision based on the current scenario and makes the system smarter. In this article, we propose an energy-efficient smart building system. The system uses the LoRa protocol for communicating the information. The system consists of compression-decompression and autonomous network models for reducing the size of the sensing information and automatically selects the suitable compression ratio of the sensing information that can be communicated to the operator with the given constraints. Our results demonstrate the impact of the proposed compression-decompression and autonomous network models on the system's delay, energy consumption, and accuracy. © 2017 IEEE.